2017
DOI: 10.1371/journal.pone.0186775
|View full text |Cite
|
Sign up to set email alerts
|

Change in the immune function of porcine iliac artery endothelial cells infected with porcine circovirus type 2 and its inhibition on monocyte derived dendritic cells maturation

Abstract: Porcine circovirus-associated disease is caused by porcine circovirus type 2 (PCV2) infection, which targets iliac artery endothelial cells (PIECs); it leads to severe immunopathologies and is associated with major economic losses in the porcine industry. Here, we report that in vitro PCV2 infection of PIECs causes cell injury, which affects DC function as well as adaptive immunity. Specifically, PCV2 infection downregulated PIEC antigen-presenting molecule expression, upregulated cytokines involved in the imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…It is reported that endothelial-derived IL-8, with a pentapeptide AVLPR extension at the NH2-terminus [5], has different biological function compared with monocyte-derived IL-8 [6]. Our previous reports also showed that the endothelial IL-8 upregulated by PCV2 infection could inhibit the maturation and antigen presentation of dendritic cells [4,7].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…It is reported that endothelial-derived IL-8, with a pentapeptide AVLPR extension at the NH2-terminus [5], has different biological function compared with monocyte-derived IL-8 [6]. Our previous reports also showed that the endothelial IL-8 upregulated by PCV2 infection could inhibit the maturation and antigen presentation of dendritic cells [4,7].…”
Section: Introductionmentioning
confidence: 96%
“…In addition, endothelial cell disfunction and vascular system disorders are also the main symptoms of porcine circovirus disease (PCVD) [2]. The PCV2-infected endothelial cells can regulate leukocyte migration, inflammatory responses [3] and induce the production of endothelial-derived IL-8 [4]. It is reported that endothelial-derived IL-8, with a pentapeptide AVLPR extension at the NH2-terminus [5], has different biological function compared with monocyte-derived IL-8 [6].…”
Section: Introductionmentioning
confidence: 99%
“…The viral stock was prepared in PK-15 cells with a titer of 10 5.5 TCID 50 /ml. Six healthy, 21-day-old, Large White-Dutch Landrace crossbred weaning piglets were used and their treatment methods at the end of the experiment were consistent with those used previously [21], that is, the piglets were euthanized by intravenously injecting an excess of sodium pentobarbital (70 ± 80 mg/kg, Sinopharm Chemical Reagent Beijing Co., Beijing, China).…”
Section: Methodsmentioning
confidence: 99%
“…PCV2 can cause arterial endotheliitis in infected pigs and can be detected in endothelial cells [20]. Porcine iliac artery endothelial cells (PIECs) can inhibit the maturation of monocyte-derived DCs (MoDCs), and PCV2-infected PIECs can further inhibit MoDC maturation, while PCV2-infected PIECs can highly express endothelial IL-8 [21]. Therefore, this study used two different co-culture methods to detect the changes in MoDCs by flow cytometry, molecular probe labeling, fluorescence quantitative PCR, and the MTS assay.…”
Section: Introductionmentioning
confidence: 99%
“…Even if the virus did not directly modulate moDC function, their function was impaired by co-culture with PCV-2 infected porcine iliac endothelial cells (PIECs). PCV2-infected PIEC, but not the virus itself, inhibited moDC maturation (assessed by MHC II and CD80/86 expression) and weakened their ability to stimulate allogeneic T cells, which suggests that PCV2 infection of endothelial cells might represent a pathogenic mechanism of this virus [87]. In contrast, Kekarainen et al observed that PCV2 induced both IL-10 and IL-12 release by BMDC, and IL-12 secretion was triggered also by PCV2 virus-like particles [88,89].…”
Section: Dendritic Cells and Virusesmentioning
confidence: 99%